Warisan tembikar labu sayong di Kuala Kangsar, Perak: Sejarah, perkembangan dan masa depan - Azmi Arifin,; Muhamad Luthfi Abdul Rahman,; Tarmiji Masron, (Universiti Kebangsaan Malaysia, 2010)
This study examines the history and development of pottery making of ‘Labu Sayong’ in Kuala Kangsar, Perak. Pottery making activities in Perak have started in the pre-historic period and have been considered as the Malay heritage that continues to survive until now. But today it has been challenged by the emergence of pottery making using modern techniques and equipment. This development and changes have caused a major decline in the traditional pottery making activities using hand. From historical and anthropological perspective, this article attempts to show how far the process of change and modernisation of pottery making in Perak has brought a negative impact and influencing the decline of such traditional activities. Based on field studies conducted in Kuala Kangsar, Perak, it is found that up to now, the activities of traditional pottery making of ‘Labu Sayong’ in Perak has really been threatened and now there is only one family left still working on it. In conclusion, this study clearly shows the need for a more balanced policy that should be taken to ensure that modernisation will not threaten the Malay heritage which has existed since ancient times. This study also suggests a more proactive and drastic effort should be taken by the government to ensure that the heritage of the Malays will continue to survive in the future